Itch in Scabies—What Do We Know? - Ständer, Sascha; Ständer, Sonja (Frontiers in Medicine, 2021)
Scabies is a common parasitic skin infestation characterized by severe itch and a heterogenous clinical presentation. Itch, as the cardinal symptom of scabies, is imposing a high burden on affected patients and is often difficult to manage. Decreased life quality and secondary complications due to a disrupted epidermal barrier and superinfections caused by streptococci illustrate the need to treat scabies and to understand the underlying mechanisms of itch in respective patients. This review summarizes available data on itch in scabies with a special focus on the clinical aspects and its underlying pathomechanisms.